2014
DOI: 10.1111/cen.12662
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune thyroid disease in Colombian patients with systemic lupus erythematosus

Abstract: AITD is frequent in SLE and does not affect the severity of SLE. Identified risk factors will assist clinicians in the search for AITD. Our results encourage smoke-free policies in patients with SLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
40
1
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 32 publications
5
40
1
6
Order By: Relevance
“…OR = odds ratio, with 95% confidence interval in parentheses; TPO = thyroid peroxidase; Tg = thyroglobulin. Regarding SLE, a Colombian study 5 found that the prevalence of hypothyroidism was 12% in their cohort, thus corroborating our findings. A meta-analysis by Pan et al 29 showed that their SLE patients were positive for Tg antibodies 2.9 times more frequently and for TPO antibodies 2.2 times frequently than healthy controls.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…OR = odds ratio, with 95% confidence interval in parentheses; TPO = thyroid peroxidase; Tg = thyroglobulin. Regarding SLE, a Colombian study 5 found that the prevalence of hypothyroidism was 12% in their cohort, thus corroborating our findings. A meta-analysis by Pan et al 29 showed that their SLE patients were positive for Tg antibodies 2.9 times more frequently and for TPO antibodies 2.2 times frequently than healthy controls.…”
Section: Discussionsupporting
confidence: 89%
“…TPO, formerly known as microsomal antigen, is an enzyme that catalyzes iodination of the tyrosine residues of thyroglobulin to form monoiodotyrosine and diiodotyrosine. 5 TPO is found on the apical surface and cytoplasm of thyroid follicular cells. 4 Unlike Tg, TPO is capable of inducing antibody-dependent cell-mediated cytotoxicity and is considered to be more specific for autoimmune thyroid disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible explanation for the increased risk of thyroid disease in young SLE patients might be the relatively higher disease activity in these patients [43, 44]. Nevertheless, this association between SLE activity and thyroid disease shown by previous studies is still controversial owing to limitations in study design and participant numbers, making it difficult to verify their conclusions [45, 46]. Also, as mentioned above, the use of aggressive immunosuppressive agents during the early stages of the disease can contribute to the later development of overt thyroiditis [30, 47], and the maximum inflammatory response in SLE patients would be expected after the reduction in immunosuppressive therapy.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 RA hastalarında tiroid otoantikorlarının mevcudiyeti ve tiroid otoimmünitesi sık görülmüş, SLE hasta grubunda da anti-TPO %21, anti-Tg ise %10 oranında pozitif bulunmuştur. 17,18 Bu çalışmada, anti-TPO antikoru pozitif olan hastalar ve kontrol grubu olgularının hiçbirinde başka bir otoimmün hastalık, otoimmün kökenli diğer endokrinolojik patolojiler ve polikistik over sendromu görülmemiştir.…”
Section: Discussionunclassified